Associations of somatic depressive symptoms with food attentional bias and eating behaviors. (1st December 2021) - Shell, Aubrey L.; Jackson, Rachel A.; Patel, Jay S.; Hirsh, Adam T.; Cyders, Melissa A.; Stewart, Jesse C.
Abstract: Recent evidence suggests that atypical major depressive disorder (MDD) – whose key features include the reversed somatic symptoms of hyperphagia (increased appetite) and hypersomnia (increased sleep) – is a stronger predictor of future obesity than other MDD subtypes. The mechanisms underlying this relationship are unclear. The present study sought to elucidate whether the individual symptoms of hyperphagia, hypersomnia, poor appetite, and disturbed sleep have differential relationships with food attentional bias, emotional eating, external eating, and restrained eating. This cross-sectional laboratory study involved 103 young adults without obesity (mean age = 20 years, 79% female, 26% non-White, mean BMI = 23.4 kg/m 2 ). We measured total depressive symptom severity and individual symptoms of hyperphagia, poor appetite, and disturbed sleep using the Hopkins Symptom Checklist-20 (SCL-20) and added an item to assess hypersomnia; food attentional bias using a Food Stroop task; and self-reported eating behaviors using the Dutch Eating Behavior Questionnaire. Hyperphagia was positively associated with emotional eating but negatively associated with food attentional bias. Hypersomnia was negatively associated with emotional eating. Poor appetite was negatively associated with emotional eating. Disturbed sleep was positively associated with food attentional bias and emotional eating. An aggregate of the remaining 15 depressive symptoms (SCL-15) was positively associated with emotional and restrained eating. Our findings highlight the importance of examining the direction of somatic depressive symptoms, and they set the stage for future research to identify subgroups of people with depression at greatest risk for obesity (e.g., those with hyperphagia and/or disturbed sleep) and the mechanisms responsible for this elevated risk (e.g., emotional eating).